2015
DOI: 10.1002/elsc.201400144
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric poly(vinylidene fluoride) microstructure and poling state in active tissue engineering

Abstract: Tissue engineering strategies rely on suitable membranes and scaffolds, providing the necessary physicochemical stimuli to specific cells. This review summarizes the main results on piezoelectric polymers, in particular poly(vinylidene fluoride), for muscle and bone cell culture. Further, the relevance of polymer microstructure and surface charge on cell response is demonstrated. Together with the necessary biochemical cues, the proper design of piezoelectric polymers can open the way to novel and more reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 48 publications
1
95
0
Order By: Relevance
“…The quantitative analysis (Figure f) demonstrated a significantly higher mineralization values in group L. Overall, both ALP and alizarin red staining demonstrated that the P(VDF‐TrFE) membranes with a zeta potential s around −53 mV and d 33 = 10 pC N −1 (group L) had the best osteoinductive capability. The d 33 = 20 pC N −1 samples, whose zeta potential was around −78 mV (group H), had the lowest osteogenesis ability, even though their surface potential was in the range of the physiological potential . The results implied that osteogenesis could be enhanced in a specific electric microenvironment within the scope of the physiological potential.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The quantitative analysis (Figure f) demonstrated a significantly higher mineralization values in group L. Overall, both ALP and alizarin red staining demonstrated that the P(VDF‐TrFE) membranes with a zeta potential s around −53 mV and d 33 = 10 pC N −1 (group L) had the best osteoinductive capability. The d 33 = 20 pC N −1 samples, whose zeta potential was around −78 mV (group H), had the lowest osteogenesis ability, even though their surface potential was in the range of the physiological potential . The results implied that osteogenesis could be enhanced in a specific electric microenvironment within the scope of the physiological potential.…”
Section: Resultsmentioning
confidence: 93%
“…Analysis of Masson's trichrome staining revealed that after 8 weeks of implantation, in group L, mature osteoid tissue was present in the top center region of the defect (Figure e). These results indicated that the membranes of −53 mV, whose d 33 was 10 pC N −1 could provide better electrical stimuli for bone regeneration compared with those of −78 mV whose d 33 was 20 pC N −1 , despite the group H membranes providing a surface potential that was also in the range of physiological bone tissue potential . This implied that regeneration of different tissues might have their own optimal electrical environment.…”
Section: Resultsmentioning
confidence: 96%
“…The cells cultured on PVDF films show an irregular morphology and random arrangement, while elongated morphology along the direction of the oriented PVDF fibers was verified when cultured on fiber membranes [31]. Thus, the polymer microstructure shows play an important role in the cell adhesion and morphology, once the cells are highly sensitive to their surrounding [42]. In relation to the membranes used in this work, as mentioned above, C2C12 cells maintain, as verified in PVDF films, a random arrangement on all membranes, independently of the different microstructures.…”
Section: Cell Proliferation and Morphologymentioning
confidence: 80%
“…Particularly for neural and muscle applications, TE fibrous scaffolds have been designed to support and guide the longitudinal cells extension along their natural axis of growth [18]. Oriented and random electrospun fibers with small pore size, density and high surface area can be obtained by electrospinning, similarly to the electrospray method, when solution viscosity is high enough (in the range of 650-2500 cP) [19]. The electrospinning process allows to effectively obtain PVDF and PLLA random and oriented fibers using a static and a rotating collector, respectively, with average diameters ranging from ~500-900 nm [11,20].…”
Section: Piezo-and Magnetoelectric Biomaterials and Structuresmentioning
confidence: 99%
“…PVDF and its copolymers are the piezoelectric polymer most used for TE applications due to their larger piezoelectric response [19]. In particular, most of the studies describing cell response under dynamic stimulation use PVDF as a support for the cell proliferation and differentiation.…”
Section: Tissue Engineering Based On Piezo-and Magnetoelectric Biomatmentioning
confidence: 99%